2023
DOI: 10.56093/ijas.v93i1.124838
|View full text |Cite
|
Sign up to set email alerts
|

Carbon capture and sequestration for sustainable land use – A review

Abstract: Carbon sequestration (CS) has been increasingly viewed as one of the crucial issues/strategies to address the challenging issues of global warming led climate change effects besides imparting sustainability to productivity. In agricultural land use systems, increased CO2 emission into the atmosphere is through repeated and frequent cultivation of croplands, crop residues, biomass burning, shifting cultivation, cultivation of low biomass producing crop cultivars, land degradation, deforestation, etc. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Several researchers [17][18] documented the role of the Agricultural produce marketing committee in promoting agricultural marketing in different states in India. No doubt, the above studies concluded that the APMCs had done a lot for farmers but still the farmers were exploited by middlemen and moneylenders from whom they get money for their dayto-day activities and agriculture expenses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers [17][18] documented the role of the Agricultural produce marketing committee in promoting agricultural marketing in different states in India. No doubt, the above studies concluded that the APMCs had done a lot for farmers but still the farmers were exploited by middlemen and moneylenders from whom they get money for their dayto-day activities and agriculture expenses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[12] The process involves capturing CO 2 and storing it underground in deep saline or depleted hydrocarbon reservoirs, preventing it from being released into the atmosphere. [13] This technique is being explored by oil and gas companies to reduce their CO 2 footprint. [14] In agricultural land use systems, carbon sequestration in soils can help offset CO 2 emissions and enhance productivity.…”
Section: Introductionmentioning
confidence: 99%
“…12 The process involves capturing CO2 and storing it underground in deep saline or depleted hydrocarbon reservoirs, preventing it from being released into the atmosphere. 13 This technique is being explored by oil and gas companies to reduce their CO2 footprint. 14 In agricultural land use systems, carbon sequestration in soils can help offset CO2 emissions and enhance productivity.…”
Section: Introductionmentioning
confidence: 99%